Controlled Release of (SBA-15)-Carvedilol Drug - Ma, Yu-Qin; Zhai, Qing-Zhou; Geng, Hao (Asian Journal of Chemistry, 2013)
In this paper, the SBA-15 molecular sieve was prepared by hydrothermal method. Carvedilol was loaded in the SBA-15 with impregnation method and the loading capacity of carvedilol is 443.50 mg/g. By means of chemical analysis, powder X-ray diffraction and low-temperature nitrogen adsorption-desorption technique at 77 K, the products were characterized. The results showed that carvedilol guest molecules had been successfully encapsulated into the channels of SBA-15. A research of the slow release effect of carvedilol encapsulated in SBA-15 mesoporous material was studied in simulated body fluid. The drug cumulative release is 19.6 % in 1 h and release 99.3 % after 32 h and tended to tranquilization. The drug release has tended to tranquilization to 19.2% after 4 h in simulated gastric fluid and to 63.2 % after 8 h in simulated intestinal fluid.